Powers of persuasion - Fletcher, Winston (Oxford University Press, 2008)
Yet no history of British advertising covering this heady period has previously been published. During the 1970s and 1980s British advertising creativity led the world. But Powers of Persuasion is not just about advertisements-- it is about advertising. In the second half of the last century Britain was also a world leader in setting industry benchmarks--innovating the disciplines of account planning and market research, setting the standard for public service advertising, launching global advertising awards festivals, introducing the best system of advertising regulation, setting up the world's largest advertising archive, and the most comprehensive on-line advertising research databank in the world. All these were the keystones on which British creativity was build. Simultaneously, British advertising companies--particularly Saatchi & Saatchi and WPP--took their place among the world's greatest